CA16112 - Luxemburg 2019 2019
DOI: 10.3390/proceedings2019011009
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of High Pressure Processing on Antioxidant Activity of Irish Potato Cultivars

Abstract: The effect of High Pressure Processing (HPP) on Irish potato cultivars’ antioxidant activity (AOA) was examined. High Pressure Processing at 600 MPa for 3 min was applied to two coloured (Rooster and Kerr’s Pink) and two white (Saxon and Gemson) Irish potato varieties. Antioxidant activity was assayed spectrophotometrically by ferric reducing antioxidant power and diphenyl-1-picrylhydrazyl methods. No statistically significant (p ≥ 0.05) change in antioxidant activity was observed in both the AOA methods irres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…The antioxidant activity (AOA) of minimally processed potatoes, estimated by both the assays, varied depending on the cultivar and the type of the treatment, but changes were statistically insignificant after HPP or HPP/US treatment. These results are consistent with a previously published study on the impact of HPP at 600 MPa on the AOA of Irish potato cultivars [ 15 ]. Insignificant ( p > 0.05) changes had been observed in the AOA of aronia berry puree after HPP at 400 and 600 MPa [ 39 ], in mango nectars after HPP at 600 MPa [ 30 ], and in sweet potato nectar [ 24 ].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The antioxidant activity (AOA) of minimally processed potatoes, estimated by both the assays, varied depending on the cultivar and the type of the treatment, but changes were statistically insignificant after HPP or HPP/US treatment. These results are consistent with a previously published study on the impact of HPP at 600 MPa on the AOA of Irish potato cultivars [ 15 ]. Insignificant ( p > 0.05) changes had been observed in the AOA of aronia berry puree after HPP at 400 and 600 MPa [ 39 ], in mango nectars after HPP at 600 MPa [ 30 ], and in sweet potato nectar [ 24 ].…”
Section: Resultssupporting
confidence: 93%
“…Potato tubers of the two cultivars, free of defects, were washed, hand-peeled, packaged in polyethylene/polyamide pouches and then vacuum sealed. HPP treatment was performed at 600 MPa (6000 bar) for 3 min at 10.6 °C (maximum temperature reached) as described in previous studies [ 14 , 15 ]. A commercial-scale high-pressure process (Hiperbaric 55HT, Miami, FL, USA) was used, located at HPP Tolling (St. Margaret’s, Co. Dublin, Ireland).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HPP significantly increased the total phenolic content (TPC) by approximately 21%, 24%, 23%, and 17% in Saxon, Gemson, Rooster, and Kerr’s Pink potatoes, respectively, with respect to those untreated (Table 2). However, changes in the antioxidant activities were non-significant between the HPP treated and untreated potatoes [25], which was also observed by Wang et al 2012 in purple sweet potato nectars following HPP treatments. Significant increases in the TPC values following the HPP treatments have been observed in several fruits (or their products) and vegetables, including smoothies [17], pumpkins [24], pomegranate juices [10], fruit juice beverages [15], and strawberry puree [7].…”
Section: Resultsmentioning
confidence: 75%
“…Currently, HPP has been successfully employed to various fruit and vegetable purées and juices [7,8,9,10,11,12,13,14], fruit juice based beverages [15,16], smoothies [17], milk [18,19] cocoyam, Peruvian carrot and sweet potato [20] purple sweet potato nectar [21], peaches [22,23], and pumpkin [24]. In our previous work, we have shown that HPP had no significant ( p > 0.05) impact on the antioxidant activity of potatoes [25]. However, the effect of HPP on PPO inactivation, proximate composition, and bioactive phytochemicals (polyphenols and glycoalkaloids) of potatoes has not been explored.…”
Section: Introductionmentioning
confidence: 99%